Indonesia Government Policy Strategy to Support Autonomous Vehicles Implementation for Public Transport - Rasdiyanti, Aprilia Dwi; Hayat, Hayat; Suyeno, Suyeno (Universitas Muhammadiyah Ponorogo, 2024)
Autonomous vehicles are now a unique and modern new trend in the development of public transport. Its application in various countries such as China, South Korea, Germany, and the United States is interesting to study from policy to implementation. Indonesia also has a great opportunity to develop autonomous vehicles to reach level 3 to 5, considering that the New Capital City (IKN) also has plans to use Integrated Transport System (ITS) and autonomous vehicles as public transport in the future. However, challenges and obstacles such as road facilities, cybersecurity threats, and public indiscipline can be a barrier to the implementation of autonomous vehicles in Indonesia. Therefore, this article aims to take a deeper look into the needs that Indonesia needs to make a policy on autonomous vehicles as public transport in the future.